Peran Media Center Solo Terhadap Pencitraan Keluarga Presiden Ir. H. Joko Widodo (Studi Deskriptif Kualitatif Peran Media Center Solo Pada Pernikahan Putra Presiden Ir. H. Joko Widodo Terhadap Citra Keluarga Presiden). - Arla, Tiara Sashita; Drs. JokoSutarso, S.E., M.Si, Drs. JokoSutarso, S.E., M.Si (2016)
Since President Jokowi became media attentions in Indonesia and overseas, it make his members of his family have also been public attention. Every good and bad news raised media, will have an impact to imaging Jokowi and family. The image of either possesed by president and his family currently make them very carefull in doing various thing on of them is a marriage on Gibran and Selvi, so that there is no longer negative news about the president and family, so as not effects the image of Ir. H. Joko Widodo and family at that time. This research aims to understand the role of Media Center Solo in order to realize the family image president in marriage the son of President Ir. H. Joko Widodo. Researchers used descriptive qualitative approach, with data collection method using the interview and observation. Data analysis tecnique used in this research is an interactive model analysis technique and use of triangulation data for data validity. The research couls be drawn the conchusion that Media Center Solo established to manage the news emerged during the marriage process Gibran with Selvi and well managed by some people that has been chosen by the personal and president. The function of Media Center Solo also to help wedding events son of president as data processing media and the formation of positive image of Java as family, simple family, and close to the people.